A reconstruction of the Late Holocene environment using archaeological charcoal from Klasies River main site cave 1, southern Cape - Zwane, Bongekile Nomasonto Patience (My University, 2018)
In this study, late Holocene environmental conditions around Klasies River cave 1, Tsitsikamma Coast, are reconstructed using archaeological charcoal that is dated to 2300 BP. The microanatomy of the archaeological charcoal remains was studied in detail under high-resolution stereomicroscopy and compared with woody species from the contemporary Tsitsikamma landscape. The results indicate that the archaeological landscape supported woody vegetation species that are adapted mostly to year-round and summer rainfall conditions. The archaeological woody species assemblage includes two species, Protorhus longifolia and Hibiscus cf. tiliaceus, that do no occur on the Tsitsikamma Coast today; they occur further north along the east coast of South Africa. The presence of both these species in the archaeological wood assemblage seems to indicate that current environmental conditions around the site are no longer suitable for their growth. Wood vulnerability indices were also calculated from measurements of the vascular microstructure of the archaeological species. These indices indicate that some archaeological species were highly vulnerable to water scarcity. This implies that woody vegetation at Klasies River 2300 BP grew under conditions with higher rainfall and less aridity relative to the present. While there is a suggestion that the late Holocene vegetation is different and the environment more mesic, this cannot be argued with certainty due to the small sample of charcoal in this study.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science , June 2018
Keywords: Geology, Stratigraphic--Holocene; Forest ecology; Charcoal--Environmental aspects; Xylem